2015
DOI: 10.1080/19476337.2015.1035673
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of free fatty acids, free amino acids, and volatile compounds of milk bases fermented byLactobacillus caseiGBHM-21 with different fat levels

Abstract: Milk fat content is an important factor affecting the flavor of fermented dairy products. The effects of milk fat concentration (0-90) g·L −1 on the changes of flavor-related compounds in the milk base fermented by Lactobacillus casei GBHM-21 were investigated. The amount of some of the free fatty acids (FFAs) and free amino acids (FFAs) increased as the fat concentration increased, accompanied by a concomitant increase of the quantities and intensities of volatile compounds (VCs). A substantial increase in lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
1
6
1
3
Order By: Relevance
“…Acetic acid was significantly (p < 0.05) higher in fermented milks than in unfermented milk ( Table 2). It has been reported that acetic acid gives a pungent, acidic, sharp vinegar-like aroma to milk [17,36,37]. Acetic acid has been previously identified in unfermented milk samples [38,39] and in several fermented milks, such as a milk fermented with Lactobacillus pentosus (15), Lactobacillus casei DN-114 001 [38], Streptococcus thermophilus IMAU80842 and Lactobacillus delbrueckii ssp.…”
Section: Identification and Chemical Groups Of Volatile Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetic acid was significantly (p < 0.05) higher in fermented milks than in unfermented milk ( Table 2). It has been reported that acetic acid gives a pungent, acidic, sharp vinegar-like aroma to milk [17,36,37]. Acetic acid has been previously identified in unfermented milk samples [38,39] and in several fermented milks, such as a milk fermented with Lactobacillus pentosus (15), Lactobacillus casei DN-114 001 [38], Streptococcus thermophilus IMAU80842 and Lactobacillus delbrueckii ssp.…”
Section: Identification and Chemical Groups Of Volatile Compoundsmentioning
confidence: 99%
“…Acetic acid has been previously identified in unfermented milk samples [38,39] and in several fermented milks, such as a milk fermented with Lactobacillus pentosus (15), Lactobacillus casei DN-114 001 [38], Streptococcus thermophilus IMAU80842 and Lactobacillus delbrueckii ssp. bulgaricus IMAU20401 [40], Lactobacillus casei GBHM-21 [37], and Streptococcus thermophilus MGA45-4 [17].…”
Section: Identification and Chemical Groups Of Volatile Compoundsmentioning
confidence: 99%
“…Os tipos e teores de aminoácidos li vres e os teores de amônia encontrados nas diferen tes marcas de leite fermentado durante Tabela 1 -Valores médios (± desvio padrão) de pH, acidez titulável e sólidos totais de diferentes marcas de leite fermentado (na validade e vencido) obtidos no mercado consumidor de Belo Horizonte, MG BAO et al, 2016). Esta é a primeira vez que o perfil e os teores de aminoácidos e de aminas livres e amônia são comparados em leites fermentados.…”
Section: Teores De Aminoácidos Livres E Amôniaunclassified
“…A predominância de treonina e histidina nos leites fermentados das marcas A e B pode conferir ao produto o sabor amargo, característico destes aminoácidos livres (BAO et al, 2016). Por outro lado, a predominância de prolina nos leites fermentados C e D pode conferir o sabor adocicado a estes.…”
Section: Teores De Aminoácidos Livres E Amôniaunclassified
See 1 more Smart Citation